Online Education in Pakistan: Past, Present and Future - Musarrat Riaz; Masood Jawaid (University of Lahore, 2022)
The lockdown resulting from COVID-19 outbreak affected individuals and nations equally. It not only harmed the economy but also led to the total shut down of all educational activities resulting in a significant gap in learning and understanding among students worldwide. Institutions, teachers, educators and students all had to quickly respond to an unexpected and 'forced' transition from face-to-face to remote teaching. The educational institutions also had to create learning environments for students and teachers in the light of the conditions in which both universities and schools had to operate. Although it leads to a number of challenges, but also provided opportunities that can best be described as blessing in disguise.